CARLOS ROBERTO ANTUNES DOS SANTOS AND THE HISTORY OF FOOD IN THE PARANÁ - Pilla, Maria Cecília Barreto Amorim; Ribeiro, Cilene da Silva Gomes (História: Questões e Debates, 2018)
The objective of this paper is to bring to the discussion the classic História da Alimentação no Paraná, by Carlos Roberto Antunes dos Santos, first published in 1995, promoting reflection on economic, social and political movements in the 19th century in the Province of Paraná, from the production and access to food and revealing the permanences that occur in the production and consumption marked by the game of the capitalist market. Nowadays, much of what was registered as belonging to the movements of the nineteenth century is replicated, not only in the relations of production, distribution, but also in the consumption of food, evidencing the relevance and importance of this work, which addresses persistent and recurring themes in Brazil. Given a number of current dilemmas, including food insecurity, lack of ecological sustainability and the need to ensure the human right to adequate and healthy food is poignant returning to the analysis by the author, from the trilogy he advocated - shortage, dearness and quality.